The knowledge of medical students about Extracorporeal Membrane Oxygenation (ECMO) in patients with COVID-19 (Research, Society and Development, 2021)
Objectives: To assess the knowledge of medical students on ECMO and to offer a cycle of lectures about its main particularities and application in the current COVID-19 pandemic. Methods: This is an prospective research with application of a questionnaire prepared by the authors before and after a cycle of lectures on ECMO and its use in patients with COVID-19. The responses of academics were compared before and after the cycle of lectures offered by the authors. Results: Calculating the average point of the sum of points obtained in the questionnaire before and after the lecture cycle, it is observed that without the lecture cycle the average point of correct answers was 10.83, whereas after the lecture cycle it went to 14.91. The Wilcoxon test proved a statistical difference between the points obtained in the questionnaire before and after the course (p=0.039). Conclusion: The importance of inserting extracurricular themes in medical education can be seen, especially regarding current issues, such as the case of new therapeutic approaches for patients with COVID.